Medellín 1968 não caiu do céu - Hoornaert, Eduardo (Revista Eclesiástica Brasileira, 2018)
Não se compreende Medellín 1968 sem o Concílio Vaticano II 1962-1965, nem esse último sem se referir à história precedente do cristianismo. Medellín 1968 tem, por conseguinte, uma dimensão de séculos. Quando regressamos para tempos muito remotos e contemplamos a tradição cristã em termos de milênios, percebemos que há, desde os inícios, um movimento em direção à constituição de uma Igreja “autocentrada” (como diria o Papa Francisco), ou seja, ao abandono de temas sociais. Isso já se percebe no primeiro grande conflito do emergente movimento de Jesus, em torno da figura de Marcião, na Roma do século II. Ao longo dos séculos, a questão social inquieta os cristãos, mas, mesmo assim, uma Igreja resolutamente “em saída” encontra sempre resistências, principalmente por parte de uma espiritualidade desligada de questões que agitam a vida humana fora dos recintos sagrados. É nesse ponto preciso que Medellín 1968 constitui uma resoluta tomada de posição quando faz uma “opção pelo pobre”. Configura um momento que não só é fundamental para as Igrejas cristãs no continente latino-americano, mas, também e talvez principalmente, para a sociedade humana em geral, acima de clausuras religiosas, confessionais, culturais e políticas. Abstract: Medellin 1968 cannot be understood without the 19621965 Vatican Council II. Neither can the latter be understood without referring to the previous history of Christianity. Medellin 1968 has, therefore, a dimension of centuries. When we look back at very remote periods and contemplate the Christian tradition in terms of millennia, we realize that there is, from the very beginning, a movement towards the constitution of a “self-centred” Church (as Pope Francisco would say), that is to say, a disregard for social themes. This is already noticeable in the first great conflict of Jesus’ emerging movement, around the figure of Marcion, in the Rome of the second century. Throughout the centuries, the social issue worries the Christians, but, in spite of this, a Church decidedly “on the way out” always finds opposition, particularly from a spirituality disconnected from the issues that stir human life outside the sacred precincts. It is at this precise point that Medellin 1968 constitutes a resolute taking of a stand when it makes an “option for the poor”. It becomes a moment that it is not only fundamental for the Christian Churches in the Latin-American continent, but also, and maybe mostly, for human society as a whole, above the religious, confessional, cultural and political enclosures. Keywords: Church and society; Conference of Medellín; Option for the poor.